Strength and oxidation resistance of Laves phase-containing refractory Nb-Ti-Zr-Cr alloys: Effect of chemical complexity - Yurchenko, N.; Panina, E.; Moskovskikh, D.; Kapustin, D.; Zhilina, M.; Shekhawat, L.; Novikov, V.; Geller, A.; Salishchev, G.; Zherebtsov, S.; Stepanov, N. (Scripta Materialia, 2024)
For a refractory Nb-Ti-Zr-Cr alloy system, we show that the effect of increasing chemical complexity, which is accepted as the main source for unique properties of high-entropy alloys, on the strength and oxidation resistance is sensitive to the particular elements added. A transition from pure Nb to NbTi and then to NbTiZr alloys that retained a single-phase body-centred cubic (bcc) structure improved the ambient-to-high-temperature strength and oxidation resistance at 1000 °C. However, the further addition of Cr that resulted in the Laves phase formation broke the trend. In the case of dual-phase bcc + Laves phase alloys, binary Nb100-xCrx alloys were much stronger at T > 600 °C than microstructurally similar multicomponent refractory complex concentrated alloys (RCCAs). Meanwhile, ternary (NbTi)100-xCrx alloys had the best oxidation resistance due to an exclusive formation of a protective Cr2O3 layer. This study emphasises opposite strategies for designing high-performance single-phase bcc and Laves phase-containing Nb-Ti-Zr-Cr RCCAs.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Chemical complexity; Mechanical properties; Oxidation resistance; Refractory high/medium-entropy alloys; Structure